2018
DOI: 10.3201/eid2406.172102
|View full text |Cite
|
Sign up to set email alerts
|

Influenza D Virus Infection in Feral Swine Populations, United States

Abstract: Influenza D virus (IDV) has been identified in domestic cattle, swine, camelid, and small ruminant populations across North America, Europe, Asia, South America, and Africa. Our study investigated seroprevalence and transmissibility of IDV in feral swine. During 2012–2013, we evaluated feral swine populations in 4 US states; of 256 swine tested, 57 (19.1%) were IDV seropositive. Among 96 archived influenza A virus–seropositive feral swine samples collected from 16 US states during 2010–2013, 41 (42.7%) were ID… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
62
4
5

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 52 publications
(95 citation statements)
references
References 29 publications
4
62
4
5
Order By: Relevance
“…[8,27] Proximity to cattle market In wildlife, IDV has been detected only in feral swine but because of the wide range of hosts susceptible to infection, wild ruminants and other species from wildlife could play a role in transmission. [5] Proximity to water Water areas can represent focus points where cattle from different farms can have close contact between each other and with wildlife, extensive breeding being the main breeding system for cattle and small ruminants in Togo.…”
Section: Risk Factor Explanation Referencesmentioning
confidence: 99%
See 1 more Smart Citation
“…[8,27] Proximity to cattle market In wildlife, IDV has been detected only in feral swine but because of the wide range of hosts susceptible to infection, wild ruminants and other species from wildlife could play a role in transmission. [5] Proximity to water Water areas can represent focus points where cattle from different farms can have close contact between each other and with wildlife, extensive breeding being the main breeding system for cattle and small ruminants in Togo.…”
Section: Risk Factor Explanation Referencesmentioning
confidence: 99%
“…In 2011, influenza D virus (IDV) was detected for the first time in pigs with influenza-like illness in the United States [1]. Since then, several studies have shown presence of the virus or anti-IDV antibodies in other species, including cattle, small ruminants, camelids, horses, and feral-swine [2][3][4][5]. The distribution of IDV is very wide since the virus has already been detected in America [6][7][8][9], Europe [10][11][12][13], Asia [14,15], and Africa [2], although the circulation of IDV in these continents, particularly Africa, is poorly understood.…”
Section: Introductionmentioning
confidence: 99%
“…Further epidemiological studies revealed that IDVs circulate in cattle in many countries including the USA (24), Mexico (5), China (6), Japan (7, 8), France (9), Italy (10), Ireland (11), Luxembourg (12), and African countries (13). Furthermore, serological studies showed that IDV antibodies are found in pigs (14), sheep (15, 16), goats (15, 16), dromedary camels (13, 17), horses (18), and humans (19). These findings imply that IDVs are globally distributed in several animal hosts.…”
Section: Introductionmentioning
confidence: 99%
“…On the contrary, ELISA identified IAV antibodies in 182 feral swine samples while the serological subtyping identified H3N2 virus antibodies in 76 feral swine samples collected from 19 states which indicated a significant past exposure of US feral swine to the H3N2 virus [294]. Further, seroprevalence of IDV was reported in 49 feral swine samples collected from Oklahoma, Texas, Hawaii and North Carolina during October 2012-September 2013 which provided the first evidence of past IDV infections in US feral swine [295].…”
Section: United Statesmentioning
confidence: 94%